2011
DOI: 10.1007/s11846-011-0065-6
|View full text |Cite
|
Sign up to set email alerts
|

Innovation in family firms: an empirical analysis linking organizational and managerial innovation to corporate success

Abstract: Family firms play a significant role in national economies worldwide, accounting e.g. for 85% of all enterprises in the OECD countries as well as for the majority of companies in Central Europe. Previous scholarly research on family firms has mostly focused on the question of how they differ from public corporations, describing family firms as being more conservative, less risk-raking, or reluctant to grow-in sum, as being less entrepreneurial than their non-family counterparts. Similarly, the existing literat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 132 publications
(120 citation statements)
references
References 87 publications
3
110
1
6
Order By: Relevance
“…Heij et al (2012) present similar results, confirming the existence of the relationships between management innovation and organizational performancethey are mediated by exploratory and exploitative product and service innovations. Kraus et al (2012), on the other hand, partly support the hypothesis that management innovation has a positive impact on corporate success and that the positive relationship between management innovation and corporate success is higher in non-family businesses (compared to family-owned firms).…”
Section: Management Innovationsupporting
confidence: 53%
See 2 more Smart Citations
“…Heij et al (2012) present similar results, confirming the existence of the relationships between management innovation and organizational performancethey are mediated by exploratory and exploitative product and service innovations. Kraus et al (2012), on the other hand, partly support the hypothesis that management innovation has a positive impact on corporate success and that the positive relationship between management innovation and corporate success is higher in non-family businesses (compared to family-owned firms).…”
Section: Management Innovationsupporting
confidence: 53%
“…The effect of mediation between the structural dimension and the ICT dimension with enterprise performance was not detected. Table 6 The results of testing mediation with the use of Cohen and Cohen's method (Kraus et al 2012), but we should also note that some studies on the links between MI and organisational performance indicate the mediating role that different factors play in these relationships. In their study, Walker et al (2011) pointed to the variable of performance management, while Heij et al (2012) identified a mediating variable as exploratory and exploitative product and service innovations.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Their business behavior is influenced by the goals to protect the longevity of the family firm ) and the will to pass on the firm to the next generation for their own and the family's interest (Berrone et al 2012). In comparison to nonfamily firms, studies demonstrate that family firms show similar attitudes for other EO dimensions and their positive effect on financial performance, with regards to Innovativeness (Kellermanns et al 2012a;Bergfeld and Weber 2011;Kraus et al 2012b), Proactiveness (De Massis et al 2014;Zellweger and Sieger 2012;Nordqvist et al 2008) and Autonomy (Gómez-Mejía et al 2007;Habbershon and Pistrui 2002). However, research findings also indicate that EO dimensions in family firms might have to be refined, to external and internal components of Innovativeness and Autonomy (Nordqvist et al 2008;Zellweger and Sieger 2012), to different components or definitions of Risk-Taking (Gómez-Mejía et al 2007;Zellweger and Sieger 2012;Zahra 2005), with regards to the applicability of Competitive Aggressiveness (Nordqvist and Melin 2010;Lumpkin et al 2010;Kallmuenzer and Peters 2017) or depending on the age/generational context for Proactiveness (De Massis et al 2014;Martin and Lumpkin 2003).…”
Section: Theoretical Foundation 21 Entrepreneurial Orientation and Fmentioning
confidence: 99%
“…Management innovation is another major factor of influence on business performance, which despite growing academic attention is still an under-researched area Kraus et al 2012a). Contributing to family business and innovation research, this study investigates the effect of internal and external factors on a firm's innovation (Walker et al 2015;De Massis et al 2013).…”
Section: Introductionmentioning
confidence: 99%